2019
DOI: 10.1177/0309324719890868
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flexoelectric effect on nonlinear forced vibration of piezoelectric/functionally graded porous nanocomposite resting on viscoelastic foundation

Abstract: Investigation of flexoelectric effect on nonlinear forced vibration of piezoelectric/functionally graded porous nanocomposite is the objective of this study. The nanocomposite is exposed to electric voltage and external parametric excitation. First, a functionally graded porous core nanoplate is modeled and then two piezoelectric layers are glued with core. It is also rested on a visco-Pasternak foundation. Second, to derive governing equation of motion, two theories including Mindlin and Kirchhoff plate theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The vast majority of those recent contributions are devoted to the analysis of free vibrations and parametric analyses of the dependence of dynamic characteristics in systems on various details of the model, see e.g., . The second large group of papers concerns the harmonic forced vibrations, both linear [155,[214][215][216] and geometrically nonlinear [217][218][219][220][221][222][223][224][225][226][227][228][229]. The other group of contributions focuses on the vibrations forced by a moving load or a moving mass, e.g., [193,[230][231][232].…”
Section: Structural Elements On Viscoelastic Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of those recent contributions are devoted to the analysis of free vibrations and parametric analyses of the dependence of dynamic characteristics in systems on various details of the model, see e.g., . The second large group of papers concerns the harmonic forced vibrations, both linear [155,[214][215][216] and geometrically nonlinear [217][218][219][220][221][222][223][224][225][226][227][228][229]. The other group of contributions focuses on the vibrations forced by a moving load or a moving mass, e.g., [193,[230][231][232].…”
Section: Structural Elements On Viscoelastic Foundationsmentioning
confidence: 99%
“…A large variety of types of structural elements is considered, including beams [187,194,195,206,213,228,232], plates [193,202,203,214,218,220,227], shells [204], composite beams [186,198,201,207,211,215,224,225], composite plates [155,185,191,199,200,210,212,222,223,226], composite shells [190,216,219,221], nanobeams [184,189,196], FG nanoplates [192,197,208,[229][230][231], and FG nanoshells/nanopanels [188,209,217].…”
Section: Structural Elements On Viscoelastic Foundationsmentioning
confidence: 99%
“…Yan and Jiang (2012a) and Yan and Jiang (2012b) investigated the influences of surface parameters on the static bending, vibration, and buckling behavior of a non-FGM nanoplate where they mentioned two cases, traction free boundary condition and without in-plane movement of plate's mid-plane, and reported that the residual surface stress becomes more noticeable in the latter case. By using Mindlin and Kirchhoff plate theories, Ebrahimi and Hosseini (2020) studied the effect of flexoelectricity on nonlinear forced vibration of piezoelectric FG porous composite nanoplate subjected to electric voltage and external parametric excitation without considering surface effect. They also reported that electric voltage has no influence on the performance of piezoelectric and flexoelectric properties of the material on vibrational response.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, cantilever-shaped energy harvesters and sensors, due to the presence of nonuniform strain in bending, have been vastly investigated in the past [22][23][24][25][26][27][28][29][30][31][32][33] Variable mechanical characteristics can result in varying strain distribution within the domain. A few studies have suggested the use of special composite materials to achieve variation in mechanical properties and thereby a strain gradient [34][35][36][37][38][39]. This method eliminates the need for special designs and dimensions of the devices to be employed, however, it requires an additional effort at manufacturing stage for compositional variation.…”
Section: Introductionmentioning
confidence: 99%